2020
DOI: 10.1109/access.2020.2966007
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Comparison of EMG-to-Force Methods for Multi-DoF Finger Force Prediction Using One-DoF Training

Abstract: Surface electromyography (sEMG) signal is one of the widely applied biological signals in the research field of the force intention prediction. However, due to the severe cross-talk issue of sEMG signals during fine hand contractions, few studies have related sEMG to multiple degree-of-freedom (DoF) force prediction of individual fingers simultanously. Accordingly, this study proposed methods mainly based on neural networks: Convolutional neural Network (CNN) and Recurrent Neural Network (RNN) to achieve bette… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 29 publications
(28 reference statements)
1
18
0
1
Order By: Relevance
“…The initial architecture of machine learning models was adopted from prior researches [13, 28, 33, 3537, 55]. The number of hidden layers, neurons in each hidden layer, feedback delay, input delay, convolution filtering size, pooling size, and strides were selected by trial and error (Figure 4) to have the highest regression accuracy.…”
Section: Machine Learning Modelsmentioning
confidence: 99%
“…The initial architecture of machine learning models was adopted from prior researches [13, 28, 33, 3537, 55]. The number of hidden layers, neurons in each hidden layer, feedback delay, input delay, convolution filtering size, pooling size, and strides were selected by trial and error (Figure 4) to have the highest regression accuracy.…”
Section: Machine Learning Modelsmentioning
confidence: 99%
“…Huang [ 10 ], Hu [ 11 ], and Zhang [ 12 ] employed a high-density array with 128 channels of sEMG electrodes to predict the muscle force, elbow-flexion force, and joint force, respectively. Chen et al performed a cross-comparison of sEMG to a force method based on CNN and recurrent neural network (RNN) for multi degrees of freedom finger force prediction with high-density sEMG signals (160 channels) [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…That is, the input dimension of GRNN equals to the number of features multiplied by the number of measurement positions. For different FSs and MPSs, the input dimension may be the same, such as regions 4, 6 and 13 in Fig10.Regions 4,6,13 are the result of one feature and four measurement positions, two features and two measurement positions, four features and one measurement position, respectively. Although the input dimension of these three regions is 4, the numbers of features and measurement positions are different, and the results of these regions are different in all evaluation indexes.…”
mentioning
confidence: 99%
“…Results demonstrated that the combination of CNN and long short-term memory (LSTM) network is an effective method. Apart from hand grasping, Chen et al [32] delved degrees of freedom force prediction on hand with the similar method. While both of them obtained sEMG signals with high-density electrodes, which are expensive and unnecessary [23].…”
Section: Introductionmentioning
confidence: 99%